2009
DOI: 10.1037/a0014272
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of cognitive load and adult age on the regularity of whole-body motion during treadmill walking.

Abstract: We investigated effects of concurrent cognitive task difficulty (n-back) on the regularity of whole-body movements during treadmill walking in women and men from 3 age groups (20 -30, 60 -70, and 70 -80 years old). Using principal component analysis of individual gait patterns, we separated main (regular) from residual (irregular) components of whole-body motion. Proportion of residual variance (RV) was used as an index of gait irregularity. The gait in all age groups became more regular (reduced RV) upon int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 31 publications
5
113
1
Order By: Relevance
“…Higher demands (forced attention conditions) overshadowed this beneficial effect, hindering gait control (i.e., increased variability) through attentional resource competition. However, although these findings support the dual-process account (Lövdén et al 2008;Verrel et al 2009), the fact that step variability in the most cognitively demanding FL condition did not exceed that in the control walking condition is counterintuitive in the framework of attentional resource competition. An explanation may be that walking alone already required attentional resources to not walk off the treadmill, the person regulating his/her gait by limiting deviations from a Bpreferred operating point^ (Dingwell et al 2010;Decker et al 2012;Dingwell and Cusumano 2015).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Higher demands (forced attention conditions) overshadowed this beneficial effect, hindering gait control (i.e., increased variability) through attentional resource competition. However, although these findings support the dual-process account (Lövdén et al 2008;Verrel et al 2009), the fact that step variability in the most cognitively demanding FL condition did not exceed that in the control walking condition is counterintuitive in the framework of attentional resource competition. An explanation may be that walking alone already required attentional resources to not walk off the treadmill, the person regulating his/her gait by limiting deviations from a Bpreferred operating point^ (Dingwell et al 2010;Decker et al 2012;Dingwell and Cusumano 2015).…”
Section: Discussionmentioning
confidence: 53%
“…Inversely, there was a dual-task gain in the older adults with fewer errors while walking. Some previous studies already showed increased cognitive performance when walking was performed simultaneously with a concurrent cognitive task Schaefer et al 2010;Verrel et al 2009). This effect was interpreted in terms of a general increase in arousal induced by physical activity.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations